Analysis of implementation maternal care program in independent midwife clinic in Padang - Miranie Safaringga; Hardisman Hardisman; Yulizawati Yulizawati (Universitas Andalas, 2018)
Factors that cause maternal mortality mostly focused on the physical factors like post partum bleeding, eclamsia, sepsys, and abortion complication. However, non physical factor like psychological and emotional factor rarely discussed. In fact, such factor also has important role in determine maternal mortality by causing several complication. The government has created several movement to overcome maternal mortality that caused by psycholgical and emotional factor. The movement are known as “Gerakan Asuhan Sayang Ibu”. The movement has 18 requirement to fulfill in order to prevent maternal mortality. This study aims to analyze the implementation of “Gerakan Asuhan Sayang Ibu” by Independent Midwife Clinic (BPM – Bidan Praktek Mandiri) in Padang municipality. This study uses qualitative design. Data were collected by deep interview. The study are is conducted in several BPM in Padang Region on december 2017 until february 2018. There are 3 midwives, 3 patients, and 3 family member of patient were particiapate as informant. The data analysis was performed using Triangulation method. The study shown that more than half midwife do the “Asuhan Sayang Ibu” well. The item that related to physical needs are fulfilled by mostly midwife. But the item that related to communication and emotional needs only fulfilled by several midwife. The deep exploration about management of “Asuhan Sayang Ibu” found the planning, implementation and evaluating phase did not run well properly.